2020
DOI: 10.1111/iej.13344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohol and nicotine consumption on the development of apical periodontitis in rats: a correlative micro‐computed tomographic, histological and immunohistochemical study

Abstract: AimTo evaluate the effects of alcohol and nicotine, when used alone or simultaneously, in the development of apical periodontitis induced in rats, using a correlative analytic approach with micro‐CT, histological and immunohistochemical analysis.MethodologyTwenty‐eight male Wistar rats were arranged into four groups: Control, Nicotine, Alcohol and Alcohol + Nicotine. The alcohol groups were exposed to self‐administration of a 25% alcohol solution, whilst the other groups drunk only filtered water. The nicotine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Cleaning and shaping procedures are the key factors in controlling inflammation in the root canal and periapical areas [ 25 ]. Many new endodontic instruments have been introduced and used extensively in endodontics to deliver irrigants into the area after instrumental preparation, which has been shown to be an effective way to reduce apical inflammation [ 11 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cleaning and shaping procedures are the key factors in controlling inflammation in the root canal and periapical areas [ 25 ]. Many new endodontic instruments have been introduced and used extensively in endodontics to deliver irrigants into the area after instrumental preparation, which has been shown to be an effective way to reduce apical inflammation [ 11 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A immunohistological study suggested a more intense inflammatory infiltrate, extensive areas of bone resorption and higher immunoreaction against RANKL antibodies in animals exposed to nicotine compared to not exposed specimens (Pinto et al . 2020b). It may be expected that this effect may be increased in patients with low‐immune response such as in patients taking antiresorptive medications (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that smoking induces delayed bone repair (Kubota et al 2016) and impaired inflammatory response, due to vasoconstriction and reduction of local oxygenation, restricting the inflow of nutrients and oxygenation in the local tissue (Segura-Egea et al 2015). A immunohistological study suggested a more intense inflammatory infiltrate, extensive areas of bone resorption and higher immunoreaction against RANKL antibodies in animals exposed to nicotine compared to not exposed specimens (Pinto et al 2020b). It may be expected that this effect may be increased in patients with low-immune response such as in patients taking antiresorptive medications (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking habits and excessive alcohol consumption are the main causes of preventable death in the world [146,147]. Recently, a study evaluated the influence of alcohol associated with nicotine consumption on AP in rats [148]. The result showed intense inflammatory infiltrate and greatest periapical lesion in this association.…”
Section: Alcoholismmentioning
confidence: 99%